2011
DOI: 10.4081/reumatismo.2006.187
|View full text |Cite
|
Sign up to set email alerts
|

Thalidomide in treatment of connective diseases and vasculities

Abstract: MECCANISMO D'AZIONEI meccanismi attraverso cui si esplicano le attività immunomodulatoria, antinfiammatoria e antiangiogenica della talidomide appaiono interconnessi, anche se non ancora completamente chiariti. La talidomide è capace di ridurre la quota circolante dei linfociti T CD4+ e quindi il rapporto CD4/CD8 (7-9). Favorisce l'aumento del numero delle cellule Natural Killer (NK) (10) e dei linfociti T helper 2 rispetto ai linfociti T helper 1. Inoltre, la talidomide inibisce la proliferazione di linfociti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Meanwhile, both PlGF and VEGF could be the markers of SLE activity. Internationally, therapies of antiangiogenic factors for cancer and retinopathy have been put into clinical practice, for instance, thalidomide [22, 23] has been proved to be effective to SLE in which traditional trials have proven futile. With the research development in the expression and regulation mechanisms of autoimmune diseases, angiogenic factors are very promising in becoming new laboratory indicators and new therapies, playing their vital roles in the diagnosis, targeted therapy, and prognosis of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, both PlGF and VEGF could be the markers of SLE activity. Internationally, therapies of antiangiogenic factors for cancer and retinopathy have been put into clinical practice, for instance, thalidomide [22, 23] has been proved to be effective to SLE in which traditional trials have proven futile. With the research development in the expression and regulation mechanisms of autoimmune diseases, angiogenic factors are very promising in becoming new laboratory indicators and new therapies, playing their vital roles in the diagnosis, targeted therapy, and prognosis of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Kuang et al also demonstrated that topical sunitinib ointment contributed to attenuate imiquimod-induced psoriasis-like inflammation through regulating the proliferation and apoptosis of keratinocytes via suppressing p-Stat3 and VEGF expression [156]. Besides, thalidomide effectively works in skin disorders such as BD through inhibition of VEGF- and FGF-2-mediated angiogenesis [157].…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…One review article reported that over 25 dermatologic conditions can be successfully treated with thalidomide 19 . Thalidomide inhibits tumor necrosis factor‐α (TNF‐α) and interleukin (IL)‐5, IL‐6, IL‐8 and IL‐12 production but stimulates the production of IL‐2, IL‐10 and interferon‐γ (INF‐γ) 20 . Thalidomide seems to inhibit granulocytes‐mediated tissue injury, but the mechanisms for this may involve the indirect effects of thalidomide in regulating leukocyte chemotaxis 21 .…”
Section: Discussionmentioning
confidence: 99%